Role of microRNA-208a as a diagnostic and prognostic marker in patients with ST-elevation myocardial infarction - Salama, Abou bakr Mohamed Mohamed Hammad (AUC Knowledge Fountain, 2020)
Acute Myocardial infarction (AMI) is the leading cause of death worldwide. Diagnosis of AMI depends on presenting symptoms, electrocardiogram (ECG), and cardiac troponins (cTns). Troponins are not good markers for patients presenting at the first hour of chest pain, so there is still a need for a marker that can be detected within the first hour of presentation, with high specificity and sensitivity, guide the medical decisions and give good insight on the expected prognosis. Previous studies reported miR-208a as a cardiac specific microRNA that can be detected in the plasma as early as 15 min of cardiac insult and is stable in plasma for hours. But no study has investigated its role as a predictor of primary percutaneuos coronary angiography (PCI) outcome. The study objective was to investigate the diagnostic role of miR-208a in AMI and its ability to predict the outcome of primary PCI and in-hospital major adverse events (MACE). In the present study, 75 patients presented by chest pain to Zagazig University hospitals were enrolled into 2 groups. Group 1 included 40 patients diagnosed with ST-elevation myocardial infarction and underwent primary PCI, of them 21 had sufficient reperfusion and 19 had no-reflow. Group 2 had negative cTns. Institutional review board approval and consents according to the Helsinki declaration were obtained. Plasma expression of miR-208a was assessed in both groups and patients were followed along their hospital stay (range =6-96 hours). MicroRNA-208a was found to be a good marker for diagnosis of MI (AUC= 0.926) which was not inferior to cTns. There was no value of adding miR208a to the classic clinical model. miR-208a can predict in-hospital MACE (AUC=0.871) and no reflow (AUC=0.875) after primary PCI and is significantly superior to cTns in these outcomes. We conclude that miR-208a is a good diagnostic and prognostic marker of myocardial infarction and can predict no reflow after primary PCI.